Mesoporous Organosilicas With Large Cage-Like Pores for High Efficiency Immobilization of Enzymes - Zhou, Zhou; Klupp Taylor, Robin; Kullmann, Simon; Bao, Huixin; Hartmann, Martin (Advanced Materials, 2011)
A group of hierarchically ordered PMOs with large cage-like pores are prepared with organosilica units including ethylene, ethenylene, and phenylene-bridged silanes. The structure and hydrophobicity of these materials are shown to offer significant advantages for the physical adsorption of lipase from aqueous media and also markedly enhance its activity.